PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 001 PERANAP KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Asnawi Asnawi; Gustimal Witri; Mahardi Mahardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: This research aims to improve learning outcomes fifth grade science students of SDN 001 Peranap academic year 2014 / 2015. This is subject penelian fifth grade students of SDN 001 Peranap with students numbering 24 students. Forms of research is classroom action research with two cycles. The results showed increased student learning outcomes, the value of student activity in the first cycle with an average of 66.66%. In the second cycle increased by an average of 79.16%. The activities of teachers in the first cycle by an average of 68.74%. In the second cycle increased by an average which is 79.16%. Research data showed improving student learning outcomes in which the prior action of student learning outcomes at the beginning of the data is complete 4 (16.67%) with an average of 59.16. I cycle to increase the number of students who completed of 16 people (66.66%) with an average of 71.45. Cycle II was increased again by students who completed totaling 23 people (95.83%), with an average value of 78.75.Their full learning outcome is 53.89%. By looking at the above data it can be concluded that the